Prototype Development Of Information System Customer Relationship Management Web-Based Aesthetic Beauty Clinics - Sutono Sutono; Halimah Halimah; Ochi Marshella Febriani (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Every company will definitely develop innovations that are always the latest in order to provide comfort in service to customers. Good service quality must be managed professionally, especially in managing information related to the customer. One of the means to accommodate customer data management is to develop a Customer Relationship Management (CRM) information system on Kartika Aesthetic that operates in the field of beauty clinics. As in general, customers who will take care must come directly to Kartika Aesthetic for registration. Not only that, notification of the customer's routine check schedule is also done when the customer finishes doing maintenance. Therefore, many customers forget the check date again because there is no notification or reminder about it. Notifications regarding discounts or treatment promo prices are also notified using social media Instagram and Facebook, if the customer does not have an account, then the customer does not get information about the ongoing promo or discount. With the existence of this CRM information system, it is expected to be able to help the acquisition of information needed by customers to be easy and fast in accordance with the expectations and needs of customers and to bridge the communication between Kartika Aesthetic and customers. The purpose of this research is to develop a prototype CRM information system, to test and evaluate the CRM information system that has been designed. The programming languages used in this system are Java and MySQL databases. The method for developing this information system uses the Relational Unified Process method with UML tools (use case diagrams, activity diagrams, class diagrams and Sequence diagrams). This CRM information system is designed with attention to user needs. In addition to making it easy for customers to register directly through the Prototype information system, this CRM information system enables customers to obtain information about maintenance schedules, new types of treatments and other promos easily and in accordance with and the need sof the customers.Keywords: CRM, Prototype, UML